Pesticides The Impacts of Pesticides Exposure - Stoytcheva, Margarita (IntechOpen, 2011)
Pesticides are supposed to complete their intended function without "any unreasonable risk to man or the environment". Pesticides approval and registration are performed "taking into account the economic, social and environmental costs and benefits of the use of any pesticide". The present book documents the various adverse impacts of pesticides usage: pollution, dietary intake and health effects such as birth defects, neurological disorders, cancer and hormone disruption. Risk assessment methods and the involvement of molecular modeling to the knowledge of pesticides are highlighted, too. The volume summarizes the expertise of leading specialists from all over the world.